THE MYSTICAL ESSENCE OF THE CONCEPTS OF THE PHILOSOPHY OF RECONCILIATION (Scientific journal of the Fergana State University, 2024)
The article analyzes the mystical essence of the concepts of reconciliation, peace, gratitude, harmony and discord, and reconciliation from a philosophical point of view. The role of these concepts in human improvement is justified in the views of Naqshbandi representatives.